Peningkatan Ketrampilan Pengembangan Desain Motif bagi Perajin Batik Gringsing, Kec. Palang, Kab. Tuban - Bramantijo Bramantijo; Trinil Windrowati; Mufi Mubaroh (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2023)
Community service activities for gringsing batik artisans in Desa Gesikharjo, Kec. Palang, Kab. Tuban by the Surabaya STKW Team, improve to skills of batik artisans in developing gringsing motif designs to strengthen their character as coastal batik. The development of motif designs is carried out by involving artisans in the process of generating ideas and developing motifs through FGDs and workshops. This activity was able to produce the development of the gringsing batik motif "Sam Pek Ing Tay" which has the characteristics of typical coastal batik.